Understanding the Dual Impact of Job Conflict and Work Stress on Organizational Performance Outcomes - Gunariah, Frilla; Bisri, Hasan; Yusup, Deni Kamaludin; Zaky, Muhammad; Hidayatunnisa, Nurul Fadhlya (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: Organizational changes in both internal and external environments can significantly affect employee productivity, particularly when human resources are unable to adapt effectively. This often results in workplace conflict and elevated job stress levels. This study aims to examine the impact of work conflict and job stress on employee performance at PT. Scudetto Prima Transportasi.Methodology: The research employs a descriptive-verificative method with a quantitative approach, utilizing non-probability sampling techniques on the entire employee population (75 individuals). Data were analyzed using SPSS Statistics 20.Findings: Furthermore, partial tests reveal that both independent variables independently exert a negative and significant influence on performance. These findings underscore the critical importance of effective conflict and stress management strategies in enhancing organizational productivity and employee effectiveness.Conclusion: The results indicate that work conflict and job stress have a simultaneous negative and significant effect on employee performance, accounting for 17.9% of the variance.